1993
DOI: 10.1111/j.1471-4159.1993.tb03168.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Thiamine Triphosphate in Rat Brain: Correlation with Chloride Permeability

Abstract: Our results show that a net synthesis of thiamine triphosphate (TTP) can be demonstrated in vitro using rat brain extracts. The total homogenate was preincubated with thiamine or its diphosphate derivative (TDP), centrifuged, and washed twice. With TDP ( 1 mM) as substrate, a 10-fold increase in TTP content was observed in this fraction (nuclear fraction, membrane vesicles). A smaller, but significant, increase was observed in the P2 fraction (mitochondrial/synaptosomal fraction). In view of the low TTP conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…Incorporation of Labeled P i into ThTP-The mitochondrial fraction was incubated in the presence of [ 32 P]PO 4 3Ϫ and pyruvate, and then thiamine derivatives were separated by HPLC, the ThTP peak was collected, and the specific radioactivity was determined as described previously (29). Based on the final specific radioactivity of 32 P i (9.99 GBq/mmol), the specific radioactivity of ThTP was 11.1 Ϯ 3.3 GBq/mmol (n ϭ 4).…”
Section: Thtp Synthesis Is Tightly Coupled To Electron Flow Through Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of Labeled P i into ThTP-The mitochondrial fraction was incubated in the presence of [ 32 P]PO 4 3Ϫ and pyruvate, and then thiamine derivatives were separated by HPLC, the ThTP peak was collected, and the specific radioactivity was determined as described previously (29). Based on the final specific radioactivity of 32 P i (9.99 GBq/mmol), the specific radioactivity of ThTP was 11.1 Ϯ 3.3 GBq/mmol (n ϭ 4).…”
Section: Thtp Synthesis Is Tightly Coupled To Electron Flow Through Tmentioning
confidence: 99%
“…Except for AK, we have been unable to measure any ThTPsynthesizing activity involving a soluble enzyme, but we have previously shown that when rat brain homogenates were incubated with ThDP, a significant amount of ThTP was detected in the particulate fraction containing cell debris, synaptosomes, and mitochondria (29,30).…”
mentioning
confidence: 99%
“…In addition, ThTP is believed to act as one of the messengers in cell signaling in response to cellular stress (7). Despite the relatively high turnover rate of ThTP in neural cells (8), its level is strictly maintained at a low concentration in vivo, presumably through the activity of ThTPase.…”
mentioning
confidence: 99%
“…Thiamin triphosphate (TTP) acts in nerves (and possibly also muscle) to activate a chloride ion channel. Bettendorf et al (1993bBettendorf et al ( , 1994 showed that the formation of TTP in brain-membrane-vesicle preparations was correlated with chloride uptake. In neuroblastoma cells in culture the addition of TTP results in activation of the chloride ion channel, which is not reversed by washing out, suggesting that it acts by phosphorylation of the chloride-channel protein (Bettendorf et al 1993a).…”
Section: Thiaminmentioning
confidence: 99%